Reply: De novo mutations in CLDN5: alternating hemiplegia of childhood or not? - Campbell, Matthew (My University, 2023)
We thank our colleagues Panagiotakaki et al.1 for their interest in our recent work elucidating the functional relevance of the G60R mutation in the CLDN5 gene in two unrelated cases of children presenting with alternating hemiplegia. Our study represents the first report of a dominant acting mutation in the coding sequence of the CLDN5 gene and has, we believe, major implications for our understanding of blood–brain barrier (BBB) function and tight junction biology in general. In reference to queries from patients and patient groups, we would posit that mutations in CLDN5 are most certainly not going to be a leading cause of alternating hemiplegia of childhood (AHC). However, while further research on BBB disruption and indeed the possibility of CLDN5 variants being causative of hemiplegia is war- ranted, it would not be an arduous exercise to include CLDN5 screening in any case of suspected hemiplegia or AHC in our opinion.
PUBLISHED
cited By 0